Program Psikoedukasi Kesehatan Mental Remaja di Sekolah SMK Taman Harapan: Ngobrolin Mental Health Tidak Harus Menunggu "Gila" Dulu - Raihan Saputra; Jihan Luthfi Nabillah; Putri Nur Ramdhani; Adelia Khoirunnisa; Wiji Aulia Fatihah; Ferdy Muzammil (Bumi: Jurnal Hasil Kegiatan Sosialisasi Pengabdian kepada Masyarakat, 2025)
Mental health issues among adolescents are often not handled properly due to low psychological literacy and strong social stigma. This community service activity aims to provide psychoeducation on the importance of mental health to SMK Taman Harapan students. The methods used include interactive lectures, group discussions, and simple simulations to increase students' awareness and understanding of mental health issues that are common in adolescence. The theme "Talking About Mental Health Doesn't Have to Wait Until You're Crazy First" was chosen to emphasize that discussions about mental health should be part of everyday life, not taboo. The results of the activity showed high student enthusiasm and increased understanding of the importance of maintaining mental health and seeking help when needed. This activity is expected to be the first step in creating a school environment that is more open and supportive of mental health issues.